Promoção da segurança no cuidado de enferamgem pediátrica: contribuições para o ensino técnio - Nascimento, Juliana da Silva Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study addresses the promotion of safety in the care of hospitalized children, electing as object teaching of this topic in nursing technical courses. The objective of elaborating systematic proposals to subsidize the planning of nursing technical teaching about promoting safety in the care of hospitalized children, based on specialized literature and from the perspective of active teachers in technical schools public nursing in the State of São Paulo – Brazil. Initially, integrative literature review was performed on errors, adverse events and safety promotion measures for hospital and its approach in pediatric nursing technical teaching. In the review were included 17 full papers, published January 2001 to December 2012, on nine national and eight international journals, and most of the early authors was of nurses and 15 of them have used quantitative research approach. Descriptive analysis was conducted of the data were categorised: types of errors and adverse events related to pediatric hospitalization, measures to promote patient safety in children, strategies for the inclusion of the theme of promoting patient safety in nursing formal education. Subsequently, under the qualitative research approach, semi-structured interviews was applied to 10 teachers from six schools public nursing techniques do Estado de São Paulo, linked to the Paula Souza Centre. The evidence collected were organized according to the thematic aspects of the method of content analysis, being the same analyzed according to the postulates of Paulo Freire. The themes and their respective nuclei of meaning were: Theme 1-safety of children admitted to hospitals: Children in hospitalization are exposed to different types of errors and adverse events; The team must have health profile and be able to prevent errors and adverse events with children; There must be the institutionalization of measures to promote ...

O presente estudo aborda a promoção da segurança no cuidado de crianças hospitalizadas, elegendo como objeto o ensino desse tema em cursos técnicos de enfermagem. Objetivou-se elaborar proposta sistematizada para subsidiar o planejamento de ensino técnico de enfermagem sobre promoção da segurança no cuidado de crianças hospitalizadas, com base na literatura especializada e a partir da perspectiva de docentes atuantes em escolas técnicas de enfermagem públicas do estado de São Paulo – Brasil. Inicialmente, foi realizada revisão integrativa de literatura sobre erros, eventos adversos e medidas para promoção da segurança pediátrica hospitalar e sua abordagem no ensino técnico de enfermagem. Na revisão foram incluídos 17 artigos completos, publicados de janeiro de 2001 a dezembro de 2012, em nove periódicos nacionais e oito internacionais, sendo que a maior parte dos primeiros autores era de enfermeiros e 15 deles utilizaram abordagem quantitativa de pesquisa. Realizou-se análise descritiva dos dados que foram categorizados: “Tipos de erros e eventos adversos relacionados à internação hospitalar pediátrica”, “Medidas para promoção da segurança do paciente pediátrico”, “Estratégias para a inserção do tema da promoção da segurança do paciente na educação formal de enfermagem”. Posteriormente, sob a abordagem qualitativa de pesquisa, aplicou-se entrevistas semiestruturadas a 10 docentes de seis escolas técnicas de enfermagem públicas do Estado de São Paulo, vinculadas ao Centro Paula Souza. Os depoimentos colhidos foram sistematizados conforme a vertente temática do Método de Análise de Conteúdo, sendo os mesmos analisados segundo os postulados de Paulo Freire. Os temas e seus respectivos núcleos de sentido foram: Tema 1 - Segurança de crianças internadas em hospitais: Crianças em internação hospitalar estão expostas a diferentes tipos de erros e eventos adversos; A equipe de saúde ...
Keywords: Enfermagem pediatrica; Equipe de enfermagem; Formação profissional; Crianças doentes - Assistência hospitalar; Doentes hospitalizados; Team nursing